The acute impact of a hematopoietic allograft on lung function and inflammation: a prospective observational study - Enocson, Alexandra; Hubbard, Richard; McKeever, Tricia M.; Russell, Nigel; Byrne, Jennifer; Das-Gupta, Emma; Watson, Lynne; Fogarty, Andrew W. (BioMed Central, 2013)
Background: No studies have investigated the immediate impact of receiving an allogeneic hematopoietic stem cell transplant (HSCT) on pulmonary inflammation or lung function.